Making music on the march: sledging songs of the 'heroic age' of Antarctic exploration - Philpott, C; Leane, E (Polar Record, 2016)
During the so-called heroic age of Antarctic exploration (c.18971922), various parties of meninvented songs to aid the act of sledging and to provide a mental diversion from the monotony of the task andthe physical demands it made on the human body. Songs composed in this uniquely polar musical genre typicallyincluded rhyming lyrics that were highly motivational and expressed a united identity. The lyrics were usually set tothe melodies of popular songs of the day. When voiced in unison by men out on the march, sledging songs could helpto promote team synchronisation and cohesion, and give the act of sledging (as well as the expeditions as a whole)a stronger sense of purpose and meaning. The singing of such songs, therefore, contributed in a very practical wayto the overall success of many Antarctic expeditions of the heroic age. This article examines three sledging songsdating from this period of Antarctic exploration and investigates the historical context in which they were created andperformed. It also considers what these songs reveal about the experiences of the men who participated in the sledgingjourneys and their earliest perceptions of the Antarctic environment.